2020
DOI: 10.1111/jfs.12773
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of weakly acidic electrolyzed water and modified atmosphere packaging on the shelf life and quality of farmed puffer fish (Takifugu obscurus) during cold storage

Abstract: The combined effect of weakly acidic electrolyzed water (WAEW) and modified atmosphere packaging (MAP) treatments on the quality of puffer fish (Takifugu obscurus) during cold storage was studied on aspects of microbiological activity, texture, total volatile basic nitrogen (TVB‐N), trimethylamine (TMA), free amino acids (FAAs), thiobarbituric acid reactive substance (TBARS), ATP‐related compounds and K value, volatile organic compounds (VOCs), and organoleptic properties. As a result, significantly (p < .05) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 75 publications
(99 reference statements)
3
21
0
Order By: Relevance
“…Thus, using TVC as the standard to determine the shelf life of obscure pufferfish, the shelf life of RE+PLH group exhibited 6 days longer than CK group. Similar results were reported by Li, Chen, Tan, Mei, and Xie (2020), who found that SAEW combined with modified atmosphere packaging could extend the shelf life of farmed pufferfish.…”
Section: Results and Disscussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, using TVC as the standard to determine the shelf life of obscure pufferfish, the shelf life of RE+PLH group exhibited 6 days longer than CK group. Similar results were reported by Li, Chen, Tan, Mei, and Xie (2020), who found that SAEW combined with modified atmosphere packaging could extend the shelf life of farmed pufferfish.…”
Section: Results and Disscussionsupporting
confidence: 90%
“…The initial TVB‐N content was 8.99 mgN/100 g, which was close to 8.69 mgN/100 g found by Li et al. (2020). The content of TVB‐N increased rapidly at the end of storage except RE+PLH group, which suggested that RE+ε‐PLH treatment could effectively retard TVB‐N increase and maintain the freshness of samples.…”
Section: Results and Disscussionsupporting
confidence: 87%
“…These results in agreement with Lin et al (2013) [228] indicate that AEW ice can serve as an innovative method to retain the quality of shrimps. In addition, lower TVB-N, trimethylamine (TMA), and thiobarbituric acid reactive substance (TBARS) values also reported for raw puffer fish (Takifugu obscurus) stored at 4 • C after treatment with weakly acidic EW (WAEW) and modified atmosphere packaging (MAP) [229]. Overall, Li et al (2020) [229] concluded that WAEW and MAP (60% CO 2 ; 5% O 2 ; 35% N 2 ) significantly extended the shelf life and maintained the better quality of the farmed puffer fish.…”
Section: Effects Of Ew On the Quality Of Fish And Seafoodmentioning
confidence: 97%
“…In addition, lower TVB-N, trimethylamine (TMA), and thiobarbituric acid reactive substance (TBARS) values also reported for raw puffer fish (Takifugu obscurus) stored at 4 • C after treatment with weakly acidic EW (WAEW) and modified atmosphere packaging (MAP) [229]. Overall, Li et al (2020) [229] concluded that WAEW and MAP (60% CO 2 ; 5% O 2 ; 35% N 2 ) significantly extended the shelf life and maintained the better quality of the farmed puffer fish. Khazandi et al (2017) [203] similarly reported increased shelf life of Southern Australian King George Whiting (KGW) and Tasmanian Atlantic Salmon (TAS) refrigerated (4 • C) fillets by 2 and 4 days, respectively, after treatment with pH neutral EW solution of 15 and 50%.…”
Section: Effects Of Ew On the Quality Of Fish And Seafoodmentioning
confidence: 97%
See 1 more Smart Citation